2015
DOI: 10.1007/s10853-015-8872-9
|View full text |Cite
|
Sign up to set email alerts
|

Liquid phase combustion of iron in an oxygen atmosphere

Abstract: In this article, we report an investigation of laser-initiated ignition of pure iron rods, using optical pyrometry, video observations, and analysis of metallographic cross section of quenched burning liquid on copper plates. When ignition occurs, caused by the melting of metal, the combustion takes place in the liquid. Two distinct superposed phases (L1 and L2) are identified in the liquid, according to the known phase diagram of the iron oxide system. Our observations show that the L1 and L2 phases can be ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The titanium alloy burns violently with a dazzling white light when the titanium alloy sample heated by a resistance wire reaches the ignition temperature. The titanium alloy is melted by the combustion heat and forms the L1 phase [20,21]. Because the solid solubility of the melting alloy is much higher than that of the solid alloy, a large amount of oxygen atom solutes is present in the melting alloy and reacts with it.…”
Section: Resultsmentioning
confidence: 99%
“…The titanium alloy burns violently with a dazzling white light when the titanium alloy sample heated by a resistance wire reaches the ignition temperature. The titanium alloy is melted by the combustion heat and forms the L1 phase [20,21]. Because the solid solubility of the melting alloy is much higher than that of the solid alloy, a large amount of oxygen atom solutes is present in the melting alloy and reacts with it.…”
Section: Resultsmentioning
confidence: 99%
“…With η = 3.5 · 10 −2 g cm −1 s 1 , ρ 0 = 1.2·10 −3 g cm 3 , we then find ω = −ρ 0 v 2 * /η ≈ −500 s 1 . Inserting this together with θ = 1.12 and the value u = 1 cm s 1 measured on the interval 500 ms to 700 ms into formula (27), one finds tan ϕ = 0.57 or ϕ = 30 o .…”
Section: Structure Of the Liquid Flow Near The Solid-liquid Interfacementioning
confidence: 96%
“…(27); on the other hand, as defined, u is also the speed of the upper rod end with respect to its lower end, that is, the cold metal. Therefore, θ = ρ/ρ l is to be calculated with ρ at T = T 0 .…”
Section: Structure Of the Liquid Flow Near The Solid-liquid Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Although iron oxide NPs prepared using chemical precipitation [58], flame pyrolysis [52], thermal decomposition [59] of precursors are mostly obtained as Fe 2 O 3 , during the laser ablation local physical conditions like oxygen partial pressure and heating/cooling rate strongly differ from the equilibrium conditions and non-stoichiometric phases are expected [36]. Studies regarding the iron ablation in air and water [60][61][62] have shown that during the laser illumination of the target, the dispersed nanosized droplets of melted Fe leaves the target and undergo rapid oxidation in contact with the dissociated solvent. Due to the limited oxygen diffusion across the iron droplet, the final iron oxidation state inside the forming NPs decreases with the increasing cooling rate.…”
Section: Characterization Of Fe-based Nps Colloidsmentioning
confidence: 99%